O Sistema Nacional de Crédito Rural e os impactos para a recuperação florestal no Brasil - Tejerina, Gabriela Rodrigues de Lima (2021)
Climate change is a global phenomenon resulting from the emission of greenhouse gases. In this context, Brazil signed the Paris Agreement in 2016, committing itself to reduce these emissions through its Nationally Determined Contributions (NDC): national targets that aims to mitigate the effects of climate change that must be met by 2030. Among these goals, Brazil committed itself, by 2030, to restore and reforest, for multiple uses, 12 million hectares of forests. Rural establishments may be fundamental for Brazil to achieve this objective, by promoting forest recovery in its areas, but they need public policies, such as rural credits, to make this action achieavable. In this sense, the objective of this study was to identify programs and characteristics of the beneficiaries who contracted financing for forest recovery under the National Agricultural Credit System (SNCR) for the period 2013-2019. The data were obtained from the Rural Credit Data Matrix (MDCR) of the Central Bank of Brazil, in order to determine which programs were accessed and the credit contractor gender and age group. The results showed that the majority of the beneficiaries of the credits for forest recovery were male (78.69%) and aged between 30 and 60 years. The credit programs accessed were the National Program for the Strengthening of Family Farming (Pronaf), the Program of Low Carbon Agriculture (Programa ABC) and the Financing Program in Support of Low Carbon Agriculture (FNO-ABC). These programs and their respective subprograms, focused on sustainability and the environment, were accessed by 21,574 contracts, totaling R$ 4.75 billion. These are low values, and not enough for Brazil to comply the goals of the Paris Agreement: restoring and reforesting. It is necessary to improve access and dissemination; update or create more economically attractive lines of finance; increase the resources made available for the SNCR; create and strengthen public Technical Assistance and Rural Extension (ATER) offices to act in accordance with the local reality and specificities of the beneficiary, especially if it is a woman or young person. MCDR needs to improve the data provided and be more transparent about the use of contracted credits.